DIAGNOSTIC SIGNIFICATION OF ICTERIC IN INFECTIOUS DISEASES - T. Ya. Chernobrovkina; V. V. Nikiforov; Ya. D. Yankovskaya; S. V. Burova; E. V. Kardonova; O. A. Saphonova (Архивъ внутренней медицины)
The differential diagnosis of infectious diseases for general practitioners is always a difficult process. The spectrum of clinical entities when jaundice may develop is unusually wide. First of all doctor must exclude or confirm infectious nature of the jaundice, which is dictated primarily by epidemiological rules. This report contains clinical and epidemiological characteristics of key diseases causing jaundice syndrome. Authors conducted analysis based on the data of the 18th department of the Moscow Infectious Hospital № 1 for the years 2014-2015 and revealed how common infectious diseases causing jaundice syndrome are.